Medication-Related Osteonecrosis of the Jaw with Spontaneous Hemimaxilla Exfoliation: Report of a Case in Metastatic Renal Cancer Patient under Multidrug Therapy - F. Bennardo; C. Buffone; D. Muraca; A. Antonelli; A. Giudice (Case Reports in Medicine)
Medication-related osteonecrosis of the jaw (MRONJ) is a well-recognized complication of drug therapies for bone metabolic disorders or cancer related to administration of antiresorptive (bisphosphonates and denosumab) and antiangiogenic drugs. This report describes an advanced and unusual case of stage III peri-implantitis-induced MRONJ involving the right upper jaw which was attempting to self-exfoliate. A 61-year-old male patient, rehabilitated with the placement of two implants when he was still healthy, was suffering from metastatic renal cancer previously treated with bevacizumab, interleukin-2, zoledronic acid, denosumab, cabozantinib and nivolumab. He had been under treatment of nonsurgical therapy over a year, based on antibiotic and antiseptic mouth rinse, without improvement of oral conditions. Surgical treatment consisted of massive sequestrectomy and complete surgical debridement of necrotic bone tissues. The specimen was sent for histopathologic analysis, which confirmed bone tissue necrosis with no evidence of metastatic disease. Two-month follow-up revealed a considerable life quality improvement. Although this complication is well known, the uniqueness of this case is given by its severity, related to the administration of multiple antiresorptive and antiangiogenic drugs, by the natural response of the oral cavity with the almost complete self-exfoliation of the massive necrotic zone. This case is emblematic in highlighting the controversies in the management of MRONJ, which certainly require effective collaboration of the multidisciplinary health care team that could improve patient safety and reduce the risk of developing MRONJ.